(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The study aimed at identifying practical effect of foreign direct investment in Jordan on each of gross domestic product, the rates fixed capital formation, the balance of payments, unemployment and inflation rates during the period (1995-2010). This study has relied on the use of the ordinary least squares method (ols), according to the economic model used to measure and analyzes these variables. The results of the study showed that the foreign direct investment has a weak effect on the balance of payments and inflation rates in Jordan during the period of study. As for the impact of foreign direct investment (FDI) on the formation rates of gross domestic product (GDP) and rates of fixed capital formation and the unemployment rate, it has been a positive influence during the study period in Jordan.